NARASI KOMUNIKASI PENGEMBANGAN HUBUNGAN ANTARA ANAK REMAJA PEREMPUAN DENGAN AYAH TIRI - Narayani Aberdeen, Avi; Rahardjo, Turnomo; Dwiningtyas Sulistyani, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
In remarried families, with regard to communication, most research states that the level of conflict and negative communication that occurs tends to be caused by stepparents when there are stepchildren, especially teenage girls. Teenage girls and stepfathers often experience difficulties or face obstacles when interacting and often avoid or distance themselves from each other due to different factors. However, even so, teenage girls who achieve a close relationship with their stepfather also appear, although minimally. This research aims to understand the communication narrative of relationship development between teenage girls and stepfathers. A total of three teenage female sources aged 19-21 years were interviewed to explore the process of developing their relationship from the first meeting to living with their stepfather. This research uses the Todorov narrative analysis method which has been modified by Nick Lacey and Gillespie. The research results show that there are three forms of relationships based on the experiences of teenage girls. The relationship developed without closeness due to initial rejection, attachment to his biological father, and a foreign perception towards his stepfather that could not be minimized. The relationship can achieve bonding because the stepfather seeks maximum self-disclosure interaction and persuasion and accommodates the child's ego from the start. Relationships without fulfilling emotional needs because of children's expectations of a father figure who can be a place for stories and a place to open up. Even so, communication plays a role in every process of developing a teenage girl's relationship with her stepfather, from the initial approach, supporting adjustment, to a more stable and flexible relationship after living together.